OPTIMIZATION MODELS OF THE UKRAINIAN POWER INDUSTRY - Slushaienko, Nataliia (Ekonomika, 2013)
Abstract. The paper deals with the environmental aspect of power industry development and uses unilateral and bilateral auction and games theory optimization modeling to simulate competitive market introduction to the Ukrainian electric power industry. The main goal of the research is to investigate how the transition will influence prices’, volumes’ dynamics and benefit distribution among market players while also addressing the problem of possible market fluctuations due to price sensitivity. Key words: electric power market, environment, competitive market introduction, auctions, games theory